Body mass index—percent forced vital capacity—respiratory hospitalization: new staging for idiopathic pulmonary fibrosis patients - Kishaba, Tomoo (J Thorac Dis, 2016)
BACKGROUND: Idiopathic pulmonary fibrosis (IPF) is relentless progressive interstitial lung disease. Evaluating predictor of mortality for IPF patients is crucial. The aim of this study was to evaluate the serial trend of important indicators of prognosis and create a useful staging method for IPF patients. METHODS: We retrospectively searched medical records, pulmonary function tests (PFTs), and chest high resolution computed tomography (HRCT) scans from January 1, 2008 through June 30, 2015 at our hospital. We also evaluated the same parameters 1-year later. RESULTS: We identified 65 IPF patients. The mean age was 71.9±1.8 years (range, 22–85 years). In terms of PFTs, mean percent predicted forced vital capacity (%FVC) was 69.8±2.7. Baseline mean body mass index (BMI) was 24.3±0.6 kg/mm(2). Mean survival was 39.2 months (range, 0.9–158.9 months). Cox proportional hazard ratios (HRs) showed the following to be predictors of mortality in IPF patients: 1-year BMI (HR: 0.899; 95% CI: 0.825–0.979; P=0.021); 1-year %FVC (HR: 0.932; 95% CI: 0.887–0.979; P=0.005) and 1-year respiratory hospitalization (HR: 3.307; 95% CI: 2.149–5.090; P<0.001). On the basis of these date, we created a new staging method for predicting mortality for IPF patients, consisting of delta BMI, delta %FVC and respiratory hospitalization within a year following diagnosis of IPF (BFR staging). We stratified patients into one of three groups according to the composite points. Mean survival of stages 1, 2, and 3 was 77.9 (30.8–158.9), 43.9 (0.9–145.2) and 14.8 (3.5–32) months (P<0.001), respectively. CONCLUSIONS: In our cohort of IPF patients, this new staging method, including delta BMI and delta %FVC and respiratory hospitalization within 1-year showed a clear survival difference.